Mn and Ti Co-doping of LiNiO2 to Improve Performance - Erdinç Öz; Jeff Dahn (Firat University Journal of Experimental and Computational Engineering)

(untitled)
LiNiO2 (LNO) has high capacity but suffers from structural instability and capacity fade, which limits its practical use in lithium-ion batteries. This study proposes co-doping LNO with Mn and Ti (MnTi25) as a strategy to overcome these issues. MnTi25 was thoroughly characterized, revealing improved structural stability and significantly reduced cation mixing compared to pristine LNO. The half-cell performance of MnTi25 is noteworthy, exhibiting a capacity similar to the established 4% Mn-substituted ZoomWeMn4 standard, demonstrating efficient Li-ion extraction and insertion. Additionally, full-cell testing against a graphite anode shows that MnTi25 delivers a capacity almost identical to a commercial LNO-based material. This promising achievement highlights the effectiveness of co-doping in addressing LNO's limitations while preserving its high-capacity potential. This study demonstrates that MnTi25 can be a promising cathode material for high-performance lithium-ion batteries by tailoring the material's structure through co-doping.